A revolt of the distrustful? Political trust, political protest and the democratic deficit - Edgar Grande; Daniel Saldivia Gonzatti (Journal of European Public Policy, 2025)
During recent crises in Europe, new heterogeneous protest movements have emerged that are difficult to label and classify. Existing studies suggest that the common denominator of these protesters is primarily the lack of political trust. Therefore, these new protest movements offer favourable conditions for investigating the relationship between political trust and protest disposition, and the consequences of political distrust for attitudes on democracy. Do these protests represent a `revolt of the distrustful' which intensifies the frequently invoked perception of the `democratic deficit'? Our study answers this question by focusing on protest disposition in two recent protest movements, the COVID-19 protest and the so-called `energy protest', which have been an important part of the German protest landscape in recent years. Based on new survey data, our results reveal a considerable lack of trust in the core institutions of representative democracy in Germany and that political distrust increases the readiness for protest. The consequences of distrust for democratic attitudes are ambiguous, however. A nuanced analysis of their political attitudes reveals that distrustful citizens combine demands for an extension of participatory democracy, restrictive views on immigration and minority issues, and political preferences for radical right populist parties.
Keywords: 330; Protest; political trust; mobilisation potential; democratic deficit; social movements